2012
DOI: 10.1016/j.brainres.2012.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses evoked by activation or blockade of GABAA receptors in the hypothalamic PVN are attenuated in transgenic rats with low brain angiotensinogen

Abstract: Previous evidence indicates that a balance between inhibitory gabaergic and excitatory angiotensinergic factors in the PVN is important for cardiovascular control. We investigated the cardiovascular response evoked from activation or blockade of GABA(A) receptors in the paraventricular nucleus (PVN), in transgenic rats with low brain angiotensinogen [TGR(ASrAOGEN)]. Brain Ang II and Ang-(1-7) levels were also determined. In functional experiments, TGR(ASrAOGEN) and Sprague-Dawley rats (SD, control) were anesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Thus, we used hexamethonium-induced reduction in RSNA as a marker of the sympathetic excitation based on the previous report. 17 The hexamethonium-induced reductions in RSNA and mean arterial blood pressure in CKD rats (at 0 and 2 weeks) were significantly increased, compared with those seen in sham rats. We demonstrated that the renal venous norepinephrine concentration correlated significantly with renal injury in our previous study.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, we used hexamethonium-induced reduction in RSNA as a marker of the sympathetic excitation based on the previous report. 17 The hexamethonium-induced reductions in RSNA and mean arterial blood pressure in CKD rats (at 0 and 2 weeks) were significantly increased, compared with those seen in sham rats. We demonstrated that the renal venous norepinephrine concentration correlated significantly with renal injury in our previous study.…”
Section: Discussionmentioning
confidence: 85%
“…In the present study, we used hexamethoniuminduced reduction in RSNA as a marker of sympathetic outflow based on the previous report. 17 The rats were killed by an overdose of potassium chloride at the end of each experiment to determine the background noise in the dead rats.…”
Section: Renal Nerve Recordingmentioning
confidence: 99%
“…13 Deletion of AGT specifically in the brain of mice and rats decreases BP and SNA. 2023 Thus, without a control mechanism, the generation of extracellular ANG may directly activate AT 1 receptors in this region of the brain leading to increased sympathetic outflow. 24 Consequently, expression of renin-b might provide a counter regulatory control mechanism preventing widespread conversion of extracellular AGT to ANG peptides.…”
Section: Discussionmentioning
confidence: 99%
“…These seemingly inconsistent results can be attributed to the fine-tuning role of AngII on behavioural responses, which may induce opposite effects depending on the concentration, brain region and experimental setting [49][50][51]. On the other hand, these two transgenic lineages showed lower levels of Ang-(1-7) in different areas of the brain [52,53], suggesting that lower Ang-(1-7) or a misbalance between the two peptides in particular regions may account for the behavioural impairment described in these transgenic lines. Future studies will be necessary to identify the role of each angiotensin peptide in specific brain regions related to psychiatric disorders, such as anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%